1998
DOI: 10.1074/jbc.273.13.7691
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Scrapie

Abstract: To define genes associated with or responsible for the neurodegenerative changes observed in transmissible spongiform encephalopathies, we analyzed gene expression in scrapie-infected mouse brain using "mRNA differential display." The RNA transcripts of eight genes were increased 3-8-fold in the brains of scrapie-infected animals. Five of these genes have not previously been reported to exhibit increased expression in this disease: cathepsin S, the C1q B-chain of complement, apolipoprotein D, and two previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(38 citation statements)
references
References 45 publications
(69 reference statements)
3
33
1
1
Order By: Relevance
“…Enhanced expression of ScRG-1 in the brain of scrapie-infected mice occurs concomitantly with increased expression of GFAP mRNA, a marker of astrocytosis (3). Moreover, ScRG-1 mRNA was found to be preferentially expressed in cells of glial origin and to encode a protein with a putative signal peptide (2). These observations suggest that ScRG-1 may play a role in the host response to prion-associated infections.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…Enhanced expression of ScRG-1 in the brain of scrapie-infected mice occurs concomitantly with increased expression of GFAP mRNA, a marker of astrocytosis (3). Moreover, ScRG-1 mRNA was found to be preferentially expressed in cells of glial origin and to encode a protein with a putative signal peptide (2). These observations suggest that ScRG-1 may play a role in the host response to prion-associated infections.…”
mentioning
confidence: 63%
“…Comparison of human and murine cDNA sequences indicated that introduction of a one-nucleotide gap in the murine ORF would generate an open reading frame corresponding to a protein of 98 amino acids the sequence of which would be almost identical to that encoded by the human ScRG-1 cDNA. This prompted us to clone a new mouse brain ScRG-1 cDNA from a lambda library, using as a probe the ScRG-1 cDNA clone 24 previously isolated by RACE (2). The sequence of clone 1 obtained from the library was then determined (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations